Decreased Low-Density Lipoprotein Cholesterol Level Indicates Poor Prognosis of Severe and Critical COVID-19 Patients: A Retrospective, Single-Center Study - Zhao, Mengmeng; Luo, Zhen; He, Hua; Shen, Bo; Liang, Jinjun; Zhang, Jishou; Ye, Jing; Xu, Yao; Wang, Zhen; Ye, Di; Wang, Menglong; Wan, Jun (Frontiers in Medicine, 2021)
Coronavirus disease 2019 (COVID-19) has become a global public health crisis. Reduced low-density lipoprotein cholesterol (LDL-C) levels were observed in COVID-19 patients. The present study aimed to explore the relationship between LDL-C levels and the prognosis of severe and critical COVID-19 patients. A total of 211 severe and critical COVID-19 patients were enrolled and divided into four groups according to the LDL-C levels, including 53 patients in Group A (LDL-C ≥ 2.71 mmol/L), 53 patients in Group B (2.28 ≤ LDL-C < 2.71 mmol/L), 53 patients in Group C (1.83 ≤ LDL-C < 2.28 mmol/L) and 52 patients in Group D (LDL-C < 1.83 mmol/L). LDL-C levels were lower in critically ill patients than in severe patients. The main symptoms before admission, characteristics on admission and comorbidities of enrolled patients did not differ among the four groups. Compared with patients with high LDL-C levels, patients with low LDL-C levels were more likely to have immune and inflammation dysfunction, renal dysfunction, liver dysfunction and cardiac dysfunction on admission. The proportions of patients with shock and acute cardiac injury, of those admitted to intensive care unit (ICU) and of those treated with mechanical ventilation were inversely related to LDL-C level. The mortality of COVID-19 patients increased with LDL-C reduction. Serum LDL-C levels of COVID-19 patients was negatively correlated with CRP level, but positively correlated with lymphocyte count, as shown by Pearson correlation analysis. Proportional hazard models showed that low LDL-C levels were associated with increased risk of hospitalization death, cardiac injury and admission to the ICU. Taken together, these results suggest that decreased LDL-C levels indicate poor prognosis of severe and critical COVID-19 patients.